2021
DOI: 10.1186/s13287-021-02275-z
|View full text |Cite
|
Sign up to set email alerts
|

Human placental mesenchymal stem cells ameliorate chemotherapy-induced damage in the testis by reducing apoptosis/oxidative stress and promoting autophagy

Abstract: Background The side effects of busulfan on male reproduction are serious, so fertility preservation in children undergoing busulfan treatment is a major worldwide concern. Human placental mesenchymal stem cells (hPMSCs) have advantages such as stable proliferation and lower immunogenicity that make them an ideal material for stimulating tissue repair, especially restoring spermatogenesis. The protective effects of hPMSCs in busulfan-induced Sertoli cells and in busulfan-treated mouse testes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The proapoptotic and anti-proliferative effects of busulfan were relatively rapidly reversed by the co-culture with MSCs, suggesting that MSCs release factors, which promote proliferation and inhibit apoptosis. This is in line with previous studies in animal models or in vitro systems using animal cells, where MSCs were shown to rescue radiotherapy-or chemotherapy-mediated damage in organs, such as the testis, colon, or liver [52][53][54][55]. However, the direct anti-apoptotic and pro-proliferative effect of MSCs was only demonstrated in TM4 mouse Sertoli cell line in vitro so far.…”
Section: Discussionsupporting
confidence: 91%
“…The proapoptotic and anti-proliferative effects of busulfan were relatively rapidly reversed by the co-culture with MSCs, suggesting that MSCs release factors, which promote proliferation and inhibit apoptosis. This is in line with previous studies in animal models or in vitro systems using animal cells, where MSCs were shown to rescue radiotherapy-or chemotherapy-mediated damage in organs, such as the testis, colon, or liver [52][53][54][55]. However, the direct anti-apoptotic and pro-proliferative effect of MSCs was only demonstrated in TM4 mouse Sertoli cell line in vitro so far.…”
Section: Discussionsupporting
confidence: 91%
“…For some models, it can be assumed that spermatogenesis might be restored due to paracrine stimulation provided by transplanted MSC to maintain the function of injured or dysregulated SSC niche components [ 59 ]. Moreover, the impact of paracrine factors secreted by MSCs on spermatogenesis restoration can be confirmed by the effective restoration of spermatogenesis in animal models of spermatogenesis failure after injection of human MSCs isolated from various tissues or their secretome [ [60] , [61] , [62] ].…”
Section: Application Of Mscs or Their Secretome Might Be Effective Fo...mentioning
confidence: 99%
“…To date, mesenchymal-like cells isolated from different parts of human placenta including amnion, chorion, and decidua have been used in preclinical and clinical studies to treat various diseases [ 98 , 99 ]. Among these, placenta-derived MSCs (PD-MSCs) have been used for treatment of infertility-related diseases such as premature ovarian failure (POF) [ 100 103 ], testicular failure [ 104 ], and male sexual problems such as Peyronie’s disease [ 72 ] and erectile dysfunction (ED) [ 73 ] and have promising results.…”
Section: Cell-based Therapies Of Noa By Paracrine and Anti-inflammato...mentioning
confidence: 99%